Muslim World Journal of Human Rights (De Gruyter, 2004)
Muslim World Journal of Human Rights offers a medium for scholarly debate on various aspects of the question of human rights as it relates to the Muslim World. MWJHR promises to serve as a forum in which barriers are bridged, and human rights are finally discussed with an eye on the Muslim world, in an open and creative manner.